Noise Sources of a 16 Mfps Video Camera - Nguyen, Hoang Dung (Old Journal, 2017)
We developed an ultra-high-speed and ultra-high-sensitivity image sensor operating at 16,000,000 fps at its highest frame rate with 165,000 pixels and capable of continuous imaging of 117 frames. The ultra-high-sensitivity is supported by Backside illumination and Charge Carrier Multiplication, CCM. Through evaluation of the sensor, we found problems such as hole accumulation at the backside, sensitivity adjustment along the center lines, direct intrusion of incident light to the in-situ memory area during mechanical shutter closing, etc... They obstructed the sensor performance, especially the ultra-high-sensitivity. These problems are summarized with sources of signal attenuation and other noises common to image sensors. In this paper, countermeasures to some of these problems are also proposed.